POTENCY OF ENDOPHYTIC FUNGI ISOLATED FROM Muntingia calabura AS ANTIFUNGAL SUBSTANCES AGAINST Candida parapsilosis - Agung Bimantara; Hary Widjajanti; Elisa Nurnawati (Biology Department, Faculty of Mathematics and Natural Sciences, Sriwijaya University, 2022)
Alternative is needed to overcome the problem of dandruff caused by C. parapsilosis. Endophytic fungi isolated from plants are capable of synthesizing compounds to produce various secondary metabolites. This study aimed to obtain the most active endophytic fungal isolates, determine the class of compounds, and determine the antifungal activity of the endophytic fungi (M. calabura) against C. parapsilosis. Fifteen isolates of endophytic fungi isolated from M. calabura were coded FDK1-FDK15. There was a color change in the media after 30 days of cultivation isolates of fungi. FDK4 and FDK13 have potential as antifungals. FDK13 fungal extract had the highest inhibition zone diameter of 20.00 mm. 20 eluates were obtained from the isolation of com-pounds (Thin Layer Chromatography), FDK 131, 1314, 1317, and 1320 eluates are compounds of the terpenoid group and FDK1316 eluates are phenol group compounds that are active in inhibiting yeast growth. FDK1317 was the most active compound isolate in inhibiting the growth of C. parapsilosis with an inhibition zone diameter of 12.5 mm.